2018
DOI: 10.3168/jds.2017-13699
|View full text |Cite
|
Sign up to set email alerts
|

Feeding reduced-fat dried distillers grains with solubles to lactating Holstein dairy cows does not alter milk composition or cause late blowing in cheese

Abstract: Feeding dried distillers grains with solubles (DDGS) to lactating dairy cows has been implicated as a cause of late blowing defects in the production of Swiss-style cheeses. Our objectives were (1) to test the effect of feeding reduced-fat DDGS (RF-DDGS; ∼6% fat) to lactating dairy cows on the composition of milk and on the suitability of the milk for production of baby Swiss cheese and (2) to evaluate the effect of diet on cow lactation performance. Lactating Holstein dairy cows were fed both dietary treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Small increases (not always significant) have also been reported in some studies with lactating cows (Janicek et al ., 2008; Chibisa et al ., 2012; Benchaar et al ., 2013) and it has been attributed to either the slightly increased energy density, due to higher fat content in DDGS diets, or to greater DM intake and, therefore, higher energy acquisition by the animals offered DDGS. Nevertheless, most cow studies with isoenergetic and isonitrogenous experimental diets, and similar intakes, as those applied in the present experiment, reported no effect on milk yield, when the applied inclusion level of DDGS was up to 30% DM (Abdelqader et al ., 2009; Gaillard et al ., 2017a, 2017b; Testroet et al ., 2018)…”
Section: Resultsmentioning
confidence: 99%
“…Small increases (not always significant) have also been reported in some studies with lactating cows (Janicek et al ., 2008; Chibisa et al ., 2012; Benchaar et al ., 2013) and it has been attributed to either the slightly increased energy density, due to higher fat content in DDGS diets, or to greater DM intake and, therefore, higher energy acquisition by the animals offered DDGS. Nevertheless, most cow studies with isoenergetic and isonitrogenous experimental diets, and similar intakes, as those applied in the present experiment, reported no effect on milk yield, when the applied inclusion level of DDGS was up to 30% DM (Abdelqader et al ., 2009; Gaillard et al ., 2017a, 2017b; Testroet et al ., 2018)…”
Section: Resultsmentioning
confidence: 99%
“…Schingoethe et al (2009) recommended that DDGS could be incorporated at 20% DM basis in lactating dairy cow diets. More recent research from Testroet et al (2018) showed no differences in performance when feeding a reduced-fat DDGS at 19.5% of diet dry matter. However, there are instances where feeding high-fat DDGS from 20 to 30% on DM basis to lactating dairy cows caused decreased milk fat concentration (Abdelqader et al, 2009;Hippen et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Sankarlal et al (2015) fed dried distillers grains at 0, 10, and 20% of a TMR diet to mid-lactation Holstein cows and found an increase in long-chain unsaturated fatty acids and a decrease in most medium-chain and all short-chain fatty acids in Baby Swiss cheeses. Testroet et al (2018) compared 2 different isonitrogenous and isoenergetic diets given to Feeding concentrates with different protein sources to high-yielding, mid-lactation Norwegian red cows: Effect on cheese ripening M. A. Olsen, 1 S. G. Vhile, 2 D. Porcellato, 1 A. Kidane, 2 and S. B. Skeie 1 * mid-lactation Holstein cows: a diet containing 13.5% of DM from soybean meal versus 19.5% of DM from reduced-fat dried distillers grains. They found no differences in the suitability of milk for cheese making (Baby Swiss cheese), as the quality of the produced cheeses was similar.…”
Section: Introductionmentioning
confidence: 99%